EFFECT OF RED GINGER EXTRACT (Zingiber officinale Var Rubrum) ON CHEMICAL AND ORGANOLEPTICS QUALITY OF AMBON CURUP BANANA WET “SALE” - Wuri Marsigit; Laili Susanti; Lia Marzalena (BPFP Faperta UNIB, 2019)
ABSTRACTQuality improvement of sale banana ambon curup was necessary to increase chemical and organoleptics quality and consumer preference. The purpose of this study was to determine the effect of variations in theconcentration of red ginger juice and the length of immersion on chemical quality, microbiology and organoleptic wet sale of banana ambon curup. By using (RAL) 2 factorial randomized design, the concentration of red ginger juice was 5%, 10% and 15% with a time of immersion for 20 and 10 minutes. The analytical method used was ANOVA. The results of the study found that sucrose levels were 37.56% to 57.54 %, the water content was 36.66% and 38.33%, ash content was 1.47 % to 1.87 %. The panelists preferred the average value of the whole (texture, aroma, and tate) was found in the P1T1 sample with a treatment of red ginger concentration of 0.05% and immersion time for 10 minut